Computerized Motion Sensitivity Screening Tests in a Multicountry Rural Onchocercal Community Survey in Africa - Babalola, O. E. (Medknow Publications, 2010)
PURPOSE: To determine whether the Wu–Jones Motion Sensitivity Screening Test (MSST) accurately reflects the burden of optic nerve disease in several onchoendemic communities in Africa. MATERIALS AND METHODS: The MSST was used to evaluate subjects in the communities of Raja in Sudan, Bushenyi in Uganda, Morogoro in Tanzania, and Ikon, Olomboro, and Gembu in Nigeria. Motion sensitivity was expressed as a percentage of motion detected in the individual eye, and this was averaged for the community. A perfectly normal eye would detect all motion and score 100%. RESULTS: In this study, 3858 eyes of 2072 subjects were tested. The test was completed in 76% of respondents. Acceptability was high. Average test time was 120.4 s. The overall mean motion sensitivity of all eyes tested was 88.49%, ±17.49. Using a cutoff level of 50%, 6.4% of all subjects tested were subnormal. The highest proportion of subnormals recorded was in Morogoro at 12.7%. Severe defects in a community best correlated with optic nerve disease prevalence, while the proportion of the defect from a higher cutoff level best correlated with overall ocular morbidity. A repeat examination in the next 5 years following ivermectin treatment will show the influence, if any, on community-wide MSST performance. CONCLUSION: A wide range in community scores reflected disease diversity. The MSST appears to be a useful test in community-wide screening and diagnosis as it reflects the general level of ocular pathology and specifically, optic nerve disease.